Harold Shipman - catching Dr Death - Parker, Alistair (BBC, 2014)
Harold Shipman was a loved and trusted doctor, and one of Britain's most prolific serial killers. Shipman murdered his patients with diamorphine and was meticulous about covering his tracks, but he still made mistakes. After he forged a will, the police opened an investigation. He was found guilty of fifteen murders, but he never admitted guilt.